CT Angiography Analysis of Axillary Artery Diameter versus Common Femoral Artery Diameter: Implications for Axillary Approach for Transcatheter Aortic Valve Replacement in Patients with Hostile Aortoiliac Segment and Advanced Lung Disease. (27th March 2016) - Tayal, Rajiv; Iftikhar, Humayun; LeSar, Benjamin; Patel, Rahul; Tyagi, Naveen; Cohen, Marc; Wasty, Najam
Abstract : Objective. The use of the axillary artery as an access site has lost favor in percutaneous intervention due to the success of these procedures from a radial or brachial alternative. However, these distal access points are unable to safely accommodate anything larger than a 7-French sheath. To date no studies exist describing the size of the axillary artery in relation to the common femoral artery in a patient population. We hypothesized that the axillary artery is of comparable size to the CFA in most patients and less frequently diseased. Methods. We retrospectively reviewed 110 CT scans of the thoracic and abdominal aorta done at our institution to rule out aortic dissection in which the right axillary artery, right CFA, left axillary artery, and left CFA were visualized. Images were then reconstructed using commercially available TeraRecon software and comparative measurements made of the axillary and femoral arteries. Results. In 96 patients with complete data, the mean sizes of the right and left axillary artery were slightly smaller than the left and right CFA. A direct comparison of the sizes of the axillary artery and CFA in the same patient yielded a mean difference of 1.69 mm ± 1.74. In all patients combined, the mean difference between the axillary artery and CFA was 1.88 mm on the right and 1.68 mm on the left. In 19 patients (19.8%), the axillary artery was of the same caliber as the associated CFA. In 8 of 96 patients (8.3%), the axillary artery was larger compared to the CFA. Conclusions. Although typically smaller, the axillary artery is often of comparable size to the CFA, significantly less frequently calcified or diseased, and in almost all observed cases large enough to accommodate a sheath with up to 18 French.